DETERMINING PRIORITY NEEDS OF CULINARY MICRO-ENTERPRISE CUSTOMERS IN INDONESIA THROUGH A QUALITY PERSPECTIVE - Tutur Wicaksono; Rika Fatimah P.L (STIE Pariwisata API Yogyakarta, 2020)
Determining the priority of customer needs is one of the right steps for business people to take to determine the direction of allocating their resources. In this study, affinity diagrams and tree charts are used to classify and translate the opinions of loyal customers about customer needs. The customer opinion (voice of the customer) obtained through semistructured interviews is then translated into a technical language (voice of quality) that has a relationship and correlation to existing theories. Data in the form of items of customer need, which are the result of affinity diagram analysis and tree diagrams, are then presented using a matrix that takes the left and right chamber of the House of Quality (HOQ) matrix from the Quality Function Deployment (QFD) method. Matrix that adopts the left and right chamber of HOQ matrix will display the items of customer needs and their priority level. The purpose of this study is to identify the item of customer needs and determine the priority level of customer needs for micro culinary fried rice enterprise in Indonesia. The variable Service Quality in the dimension of Responsiveness with the indicator item Fast Service ranks third. Variable Perceived Benefit in the dimension A Statement of Value with items including Low Prices and Discount occupy the second position. The variable of product quality in the Performance dimension with items including Delicacy, High Quality Ingredients, Varied Menu and Large Portion is the variable of customer needs with the highest priority.